Three-dimensional elasticity models for buckling of anisotropic and auxetic beams and plates - Hamad, Eltigani, author; Heyliger, Paul, advisor; Atadero, Rebecca, committee member; Puttlitz, Christian, committee member (Colorado State University. Libraries, 2015)
The three-dimensional elasticity model is developed to determine the critical buckling load for isotropic, anisotropic, and auxetic beams and plates. Different beam theories are studied and compared to the elasticity theory. The study was based on the assessment of those beam theories using different beam cross-sections and boundary conditions. The elasticity theory for anisotropic beams obtained well results for large slenderness ratios when it compared with Euler-Bernoulli theory which is considered in this study the main area of comparison study. For small values of slenderness ratio the elasticity theory obtained significant difference than the Euler-Bernoulli theory, which means that Euler-Bernoulli is weaker when it is used for short beams than long beams. The orientation of the anisotropy behavior is also studied and has showed how the buckling load can be changed due to the orientation of the elasticity modulus. The auxetic beams behave differently than the anisotropic behavior, it gives results higher and lower than the Euler-Bernoulli theory according to the slenderness ratio and the Poisson’s ratio values. A significant behavior was noticed in using beams with negative Poisson’s the ratio which can be useful in structure mechanics field.
Keywords: ABAQUS; anisotropic; auxetic; buckling; Euler-Bernoulli